Seedling Performance of Cocoa Genotypes (Theobroma cacao L.) in Drought Stress Condition. - Agung Wahyu Susilo; Sobir Sobir; Adinda Wuriandani; Desta Wirnas (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Drought stress can affect changes in physiological, morphological, biochemical,and molecular of plant. Plant in drought stress showed slower growthand development than in normal condition. This research aimed to determine the response of cocoa genotypes in seedling phase to drought stress in morphological and stomata character. This research conducted with split-plot design with main plot were water regimes (25% and 100% available water content). Eleven genotypes were used in this research consisted of six genotypes crosses and five genotypes parents. Variables observed were stem diameter, root volume, root length, leaf area, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, root/shoot ratio, and stomatal conductance. Drought stress decreased values associated with all observed morphological characters and stomata characters. Root/shoot ratio and stomatal conductance can be used to determine genotype with tolerance to drought. Sulawesi 3 x ICCRI 09 showed heighest in root/shoot ratio and stomatal conductance. Sulawesi 3 x ICCRI 09 can be used as candidate of plant material tolerant to drought.